Tutela e prospettive delle tecniche di allevamento mitilicole tradizionali - Portacci, Giuseppe; Di Leo, Antonella (Biologia Marina Mediterranea, 2025)
From the 16th century, the Mar Piccolo of Taranto was one of the most original site of bivalve mollusc farming. It was able to generate significant production peaks in the early 1900s. All this was achieved through ancient techniques using natural fibres. These fibres were replaced by plastic only in the 1970s. The aim of this work was to evaluate the preliminary technical and productive feasibility of recovering ancient mussel farming techniques by comparing mussels grafted with the ancient method with the current one. The better settlement percentage of the mussels grafted with the old method, compared to the current one, allowed to obtain better Condition Index. The better performance of the condition indices of the mussels grafted with the old method together with the slowness of the grafting times make it an excellent candidate both for environmental sustainability and for a production of the Slow Food Presidium, the black mussel of Taranto